Gender, Climate Change Adaptation, and Cultural Sustainability: Insights From Bangladesh - Roy, Sajal; Tandukar, Shristi; Bhattarai, Utsab (Frontiers in Climate, 2022)
The focus of this paper is mainly to investigate climate change adaptation practices and the applicability of a cultural sustainability approach in understanding gender dimension of the residents of the southwest coast of Bangladesh. It is one of the most vulnerable regions in South Asia due to the significant impacts of climate change. The long-term effects of climate change in this region are the increasing salinity in farmlands, heatwaves, and sea-level rise. The southwest coast of Bangladesh is a classic example of “good practice” as well as the center for learning, implementing, and communicating climate change adaptation actions in practice. The reason for this the collective action carried out to initiate and improve adaptation activities by the Ministry of Environment, Forest and Climate Change of the Government of Bangladesh, as well as several national and international development and non-government organizations (NGOs). Using a systematic review of literature, and field-based case studies, we examined how gender and cultural issues (such as the adaptive capacity of men and women, and the transformation of gendered power relations) have been addressed to successfully implement climate change adaptation initiatives in the context of the nominated study area. Our study results revealed that both male and female participants were strategic and capable of dealing with climate change impacts, although the adaptive capacity of the former group was comparatively sturdier than the later. The extent of cultural sustainability was found to be weaker in the study region compared to many other coastal communities in the country. The efforts made by NGOs in collaboration with the governmental bodies of Bangladesh were found contributory in providing knowledge of climate change along with the techniques to adapt to its consequences for the people of the study region. Similarly, the activities of NGOs were found influential in helping the government to support people in adapting to climate change in terms of the gendered and cultural sustainability perspectives. Our findings contribute to the field of climate change impacts in understanding the complexities of rural development.